THE RELATIVE SIGNIFICANCE OF SYNTACTIC KNOWLEDGE AND VOCABULARY KNOWLEDGE IN SECOND LANGUAGE LISTENING ABILITY. Issue 2 (May 2020) - Vafaee, Payman; Suzuki, Yuichi
Abstract: The main purpose of the current study was to examine the relative significance of vocabulary knowledge (VK) and syntactic knowledge (SK) in second language (L2) listening ability, while accounting for the effect of several cognitive and affective factors. A total of 263 English-as-a-foreign-language learners took a standardized listening test (IELTS), as well as a battery of nine linguistic (two aural SK tests and two aural VK tests—covering both breadth and depth of VK), cognitive (two working memory tests and a metacognitive knowledge questionnaire), and affective measures (two L2 listening anxiety questionnaires). Structural equation modeling analysis revealed that both VK and SK were significant predictors of L2 listening ability; however, VK was a stronger predictor with an effect size being almost twice as much as the one for SK (.55 vs. .28). The results also showed that metacognitive knowledge, working memory, and L2 listening anxiety are significant predictors of L2 listening ability.